The multilevel regulation of CD95 signaling outcome - Yurchenko, M.; Shlapatska, L.M.; Sidorenko, S.P. (Experimental Oncology, 2012)
CD95, also called Fas or APO-1, was the first death receptor (DR) identified and characterized. Studies on CD95 receptor signaling revealed the versatile principles of cell fate regulation via DR. DRs could exert both pro- and anti-apoptotic effects depending on clustering, internalization or signaling thresholds and other extracellular signals. It became clear that molecular network regulating cell death and survival is under the multilevel control. In this Review we focus on the regulation of CD95 signaling and provide brief analysis of molecular switches of its pro- and antiapoptotic functions. At least five levels of life-death cell regulation via CD95 could be tracked: extracellular, membrane, DISC, mitochondrial, and miRNA. The cellular outcome of signaling via DRs depends on other extracellular signals and availability of different intracellular components of signal transduction pathways. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.